Learning music among adults: problems and challenges / Abd Rahman Yaakop - Yaakop, Abd Rahman (Faculty of Music, 2013)
The purpose of doing this research is to investigate the problems confronted by adults who learning music and therefore to recommend ‘he solution which may help them. The problems which had been identified are me competency problem, tone deafness and practice method. The interview question was developed according to the problem detected. An analysis of primary data was collected through interviews from 8 respondent and these data were grouped into different areas of research. Suggestions on improvement within the learning process can be obtained through the analysis of this research.